Theoretical Investigation of the Effects of some Geometrical Parameters on the Performance of Wire-Plate Electrostatic Precipitator - Latif, Wisam A.; Kadhim, Mohammed O.; Ali, Qays H. (Iraqi Journal of Science, 2021)
Some geometric parameters affecting the performance of a wire-plate electrostatic precipitator (ESP) are investigated theoretically. A numerical model was built to investigate the influence of the discharge wire size, wire separation, collector plates spacing, and roughness factor on the ESP performance. The results show that thinner wires emit higher current than larger ones at the same applied voltage, which would be suitable for low voltage power supply to generate the desired current density at the collecting electrodes. The results also show that, as the discharge electrodes get closer, the corona gets suppressed, resulting in a diminished corona current flow. On the other hand, as the distance between electrodes increases, the total current density decreases, leading to a less efficient ESP performance. Narrow spacing between collector plates gives a better performance. With regard to the effect of the roughness factor, the results revealed that the emitted current is strongly affected by the wires physical conditions.